Evaluation of Hypertriglyceridemia in Critically Ill Patients With Coronavirus Disease 2019 Receiving Propofol. (11th January 2021) - Kovacevic, Mary P.; Dube, Kevin M.; Lupi, Kenneth E.; Szumita, Paul M.; DeGrado, Jeremy R.
Abstract : Objectives: To report the prevalence of, and evaluate risk factors for, the development of hypertriglyceridemia (defined as a serum triglyceride level of > 400 mg/dL) in patients with coronavirus disease 2019 who received propofol. Design: Single-center, retrospective, observational analysis. Setting: Brigham and Women's Hospital, a tertiary academic medical center in Boston, MA. Patients: All ICU patients who with coronavirus disease 19 who received propofol between March 1, 2020, and April 20, 2020. Interventions: None. Measurements and Main Results: The major outcome of this analysis was to report the prevalence of, and risk factors for, the development of hypertriglyceridemia in patients with coronavirus disease 19 who received propofol. Minor outcomes included the development of acute pancreatitis and description of propofol metrics. Of the 106 patients that were included, 60 (56.6%) developed hypertriglyceridemia, with a median time to development of 46 hours. A total of five patients had clinical suspicion of acute pancreatitis, with one patient having confirmatory imaging. There was no difference in the dose or duration of propofol in patients who developed hypertriglyceridemia compared with those who did not. In the patients who developed hypertriglyceridemia, 35 patients (58.5%) continued receiving propofol for a median duration of 105 hours. Patients who developed hypertriglyceridemia had elevated levels of inflammatory markers. Conclusions: Hypertriglyceridemia was commonly observed in critically ill patients with coronavirus disease 2019 who received propofol. Neither the cumulative dose nor duration of propofol were identified as a risk factor for the development of hypertriglyceridemia. Due to the incidence of hypertriglyceridemia in this patient population, monitoring of serum triglyceride levels should be done frequently in patients who require more than 24 hours of propofol. Many patients who developed hypertriglyceridemia were able to continue propofol in our analysis after reducing the dose.